CREATION OF PACITAN RONTEK BATIK MOTIFS IN STREETWEAR CLOTHING - Shalma Sukarni; Danang Priyanto, (Indonesian Institute of the Arts Surakarta, 2025)
The Pacitan Rontek Gugah Sahur Festival is one of the traditional arts owned by the city of Pacitan. The Rontek Gugah Sahur Festival, which is an art performance, raises the potential in a region of Pacitan Regency or outside the region as a performance concept. The first Rontek Festival was held in 2011. The theme raised in the creation of the work is the performance of the Rontek Gugah Sahur Festival which aims to increase insight, cultural appreciation of the community, and increase the unity of fellow children of the nation in the spirit of preserving Pacitan's local cultural arts. The formulations taken include: 1). how to create batik motif with the idea of Rontek Gugah Sahur Festival, 2). How to create street wear clothing in written batik works, 3). How to apply the motif design to street wear clothing. The objectives of making the work include: 1) Creating batik motifs that originate from the idea of the Pacitan Rontek Gugah Sahur Festival, 2). Creating street wear clothing in written batik from the idea of Rontek Gugah Sahur Festival, 3). Applying written batik motifs into street wear clothing from the idea of Pacitan Rontek Festival. Creating Rontek/thek Festival motifs and elements of the Festival by applying them to street wear. The method of creation used was the idea of Thunder from the exploration stage, incubation stage, conceptualization stage, and materialization stage. The Final Project that was realized had 4 fashion works. The first entitled JUMEDUL which means the beginning of the creation of the Pacitan Rontek Festival which was raised from Gugah Sahur using thethek. Second MAYANGKARA which means clothing with light drawn on the motif means that in the Gugah Sahur Rontek Festival, light is needed so that it can complete the Festival to the finish. Third MAHDI which means coolness for the conditioning of the elements in the Pacitan Rontek Festival. The fourth, BERSAJI, means togetherness in the Pacitan Rontek Festival, togetherness, cohesiveness in playing every role to the maximum.